ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PELANGGAN PADA HIJAB BILLAH DI SITUBONDO DENGAN KEPUTUSAN PEMBELIAN SEBAGAI VARIABEL INTERVENING - Syafira, Intan; Hamdun, Edy Kusnadi; Anshory, Muhammad Iqbal (Fakultas Ekonomi dan Bisnis, 2023)
Sustainability and development of a company in any form is determined by the marketing. As a company, Boutique Billah Hijab must be capable to choose the right marketing strategy in order to grow and maintain the stability of its business because it is one of the success factors. This research aimed at anayzing and testing the effects of lifestyle and brand image on customer satisfaction at Boutique Hijab Billah. The sampling technique was determined with probability sampling. Data analysis and hypothesis testing in this research employed the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using the Smart PLS 3.0 application shows that lifestyle has a significant effect on purchase decision, brand image has a significant effect on purchasing decisions, and purchase decisions have a significant effect on customer satisfaction. Meanwhile, the results of the indirect effect hypothesis test show that the lifestyle variable has a significant positive effect on customer satisfaction through purchasing decisions and brand image has a significant positive effect on customer satisfaction through purchasing decisions.